Crowd Framework Untuk Pengembangan Film Animasi 3D - ., Sukoco (Speed - Sentra Penelitian Engineering dan Edukasi, 2009)
ABSTRACT: Crowd has been widely used in a variety of commercial products games and movies. The films were well-funded, has been widely used technique to give the crowd a colossal spectacular action picture. Although it has great potential but inIndonesiathe study of the crowd is still small. This paper aims to conduct a study on developing a framework for crowd simulation in the development of 3D animation.Keywords: Animation, Framework ABSTRAK : Crowd telah banyak dipakai dalam berbagai produk komersial game dan film. Film-film yang berdana besar, telah banyak menggunakan teknik crowd untuk memberikan gambaran aksi kolosal yang spektakuler.Walaupun memiliki potensi yang besar tetapi di Indonesiastudi mengenai crowd masih sedikit. Paper ini bertujuan untuk melakukan studi mengenai framework untuk mengembangkan simulasi crowd dalam pengembangan animasi 3D.Katakunci : Animasi, Framework